2012
DOI: 10.1186/1471-2407-12-495
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in survivors of stage I-II breast cancer: randomized trial of post-operative conventional radiotherapy and hypofractionated tomotherapy

Abstract: BackgroundHealth-related quality of life (HRQOL) assessment is a key component of clinical oncology trials. However, few breast cancer trials comparing adjuvant conventional radiotherapy (CR) and hypofractionated tomotherapy (TT) have investigated HRQOL. We compared HRQOL in stage I-II breast cancer patients who were randomized to receive either CR or TT. Tomotherapy uses an integrated computed tomography scanner to improve treatment accuracy, aiming to reduce the adverse effects of radiotherapy.MethodsA total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 43 publications
2
42
1
3
Order By: Relevance
“…Chemotherapy also has been reported to predict impaired QOL in 5- and 10-year survivors. 51,52 QOL following specific adjuvant treatment regimens has been described in longitudinal studies with patients receiving radiation, 44,45,53 chemotherapy, 54 radiation and chemotherapy, 55,56 and endocrine therapy. 5760 However, unlike these studies, we included an adjuvant chemotherapy*time interaction term in our analysis—in relation to receipt of BCS or mastectomy as well—allowing us to determine if, and how, the change in QOL over time differed by receipt of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy also has been reported to predict impaired QOL in 5- and 10-year survivors. 51,52 QOL following specific adjuvant treatment regimens has been described in longitudinal studies with patients receiving radiation, 44,45,53 chemotherapy, 54 radiation and chemotherapy, 55,56 and endocrine therapy. 5760 However, unlike these studies, we included an adjuvant chemotherapy*time interaction term in our analysis—in relation to receipt of BCS or mastectomy as well—allowing us to determine if, and how, the change in QOL over time differed by receipt of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome of interest was the presence of severe fatigue at 2 years after diagnosis, defined by a score of EORTC QLQ‐C30 ≥ 40 …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the benefit of shorter treatment course on quality of life has also been suggested. In a study cohort of stage I‐II breast cancer comparing conventional and hypofractionated tomotherapy, women reported faster recovery of fatigue, and physical, cognitive, and emotional functioning scores with shorter course treatment . Evaluation of patient factors in the current analysis revealed that increasing age category, race, and stage were not associated with delivery of shorter fractionation regimens.…”
Section: Discussionmentioning
confidence: 72%
“…In a study cohort of stage I-II breast cancer comparing conventional and hypofractionated tomotherapy, women reported faster recovery of fatigue, and physical, cognitive, and emotional functioning scores with shorter course treatment. 20 Evaluation of patient factors in the current analysis revealed that increasing age category, race, and stage were not associated with delivery of shorter fractionation regimens. This is similar to findings of an analysis by Bekelman where age in patients who met ASTRO guideline indications was not significant for utilization of hypofractionation.…”
Section: Discussionmentioning
confidence: 75%